Restorative Justice as an Alternative in Resolving Severance Pay Administrative Disputes Between Employees and Companies - Nur Komala; Asyri Febriana (Journal Of Legal Studies Judex Praetor, 2025)
This study focuses on justice for workers, which includes equal, fair, and non-discriminatory treatment, where their rights are fulfilled in accordance with applicable regulations or laws. In addition, this study also highlights the importance of creating a conducive, safe, and comfortable work environment and providing career development opportunities for employees as supporters of the institution. Equally important is protection from arbitrary termination of employment by superiors, which can result in administrative losses for employees. The main focus of this study is two important things, namely the resolution of administrative disputes experienced by employees due to termination of employment, and the application of restorative justice in resolving disputes related to severance pay between employees and companies. Using a solution-oriented approach based on fairness, this study aims to provide insight into how both parties can reach a fair agreement, reduce tension in working relationships, and encourage the creation of a more harmonious work environment.